PENGARUH MANAJEMEN MODAL KERJA TERHADAP RETURN ON INVESMENT PADA PERUSAHAAN YANG TERDAFTAR DI JAKARTA ISLAMIC INDEX - Unimal, Nazir (JURNAL KEBANGSAAN, 2015)
ABSTRACTÂ This study aims to identify and analyze the impact of working capital management of the return on investment as the companies listed on the Jakarta Islamic Index. The sample in this study is a company registered in Jakarta Islamic Index of 15 companies with purposive sampling technique. Return on investment as influenced by the rotation of working capital (working capital turnover) . The faster turnover of working capital increasing the return on investment as well . Then the turnover of cash (cash turnoverÂ , the faster the cash turnover increased return on investment as . Furthermore, return on investment as well be influenced by inventory turnover (inventory turnover). The faster the inventory turnover rate increased return on investment as the companies listed on the Jakarta Islamic Index.Â Keywords : return on invesment, working capital management